(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This scientific article analyzes the development processes of the hotel industry in Uzbekistan, its strategic importance in enhancing tourism potential, and the factors contributing to increasing competitiveness in the international tourism market. Particular attention is paid to improving the quality of hotel services, implementing modern management systems, utilizing digital technologies, and enhancing the investment climate. The paper also scientifically substantiates ways to increase tourist flow through the development of regional infrastructure, improvement of personnel qualifications, and diversification of services provided.